1996
DOI: 10.1177/019262339602400620
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Diet, Ad Libitum Overfeeding, and Moderate Dietary Restriction on the Rodent Bioassay: The Uncontrolled Variable in Safety Assessment

Abstract: Ad libitum (AL) overfeeding is the most significant, uncontrolled variable affecting the outcome of the current rodent bioassay. There is a highly significant correlation between AL food consumption, the resultant obesity and body weight, and low 2-yr survival in rodents. AL feeding of diets with lowered protein, metabolizable energy (ME), and increased fiber does not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
140
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(148 citation statements)
references
References 29 publications
4
140
0
4
Order By: Relevance
“…However, depending on the intensity, duration and frequency of FR and physical activity, there may be damage to the organism [1][2][3][4][5][6][7] . Research shows that this association may depress 8 or improve cardiac performance 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, depending on the intensity, duration and frequency of FR and physical activity, there may be damage to the organism [1][2][3][4][5][6][7] . Research shows that this association may depress 8 or improve cardiac performance 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The practice of AL feeding has various widely recognized drawbacks and in rodent experiments AL feeding has been considered as the least controlled factor in biomedical studies. 1 In summary, it is rather surprising that AL feeding of laboratory mice and rats seems to be the norm all over the world.…”
mentioning
confidence: 99%
“…they make a better recovery from surgery and they exhibit reduced reactions to inflammatory agents. 1,7 The method of feeding can also affect a variety of physiological parameters in younger animals prior to changes in morbidity and mortality. DR has been shown to decrease the white blood cell count, as well as neutrophil and lymphocyte numbers, 2,8,9 whereas erythrocyte count, haematocrit and haemoglobin are reported to increase.…”
mentioning
confidence: 99%
“…Food restriction induces beneficial health effects such as increased longevity and retards or prevents a broad spectrum of agerelated pathophysiological changes such as loss of skeletal muscle mass, diabetes mellitus, hypertension, and cancer (1)(2)(3). Recent research from our laboratory has shown that 50% food restriction promotes left ventricular dysfunction and increases contraction and relaxation times in isolated papillary muscle of both young Wistar-Kyoto normotensive and spontaneously hypertensive rats (4-7).…”
mentioning
confidence: 99%